DOI: 10.3990/1.9789036535267
|View full text |Cite
|
Sign up to set email alerts
|

Image-based robotic steering of advanced flexible endoscopes and instruments

Abstract: The cover illustration shows the Anubis flexible endoscope within the gastrointestinal tract. Illustration by Derk Reilink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…A setup could have been added that allows robotic steering and shaft control (4-DOF) with a Phantom Omni controller with one hand (like setup 2 and 3) and manual control of an ANUBIS steerable instrument (Figure 1.8) with the other hand. However, research of Reilink et al [2013] already showed that robotic control is preferred if compared with manual control of a steerable instrument.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A setup could have been added that allows robotic steering and shaft control (4-DOF) with a Phantom Omni controller with one hand (like setup 2 and 3) and manual control of an ANUBIS steerable instrument (Figure 1.8) with the other hand. However, research of Reilink et al [2013] already showed that robotic control is preferred if compared with manual control of a steerable instrument.…”
Section: Methodsmentioning
confidence: 99%
“…It uses the camera image as input instead of the motor position. Reilink [2013] has conducted research on this topic. His work could be helpful in improving the intuitive mapping of hand and instrument movements.…”
Section: Input Devicementioning
confidence: 99%
See 2 more Smart Citations
“…Ruiter (2013) [30]. The use of haptic and image guidance was described in the dissertation of Dr. R. Reilink (2012) [35]. Extension of the platform using image guided navigation options was described in the dissertation of Dr. N. Van der Stap (2016) [36].…”
Section: Robotic Add-on Platformmentioning
confidence: 99%